الحجر على المرأة في مالها - الداية، سلمان بن نصر بن أحمد (عبد الفتاح محمود ادريس, 2013)
يتناول هذا البحث مسألة مهمة وهي حكم الحجر على المرأة في مالها فيما يزيد على الثلث. ضمنت المبحث الأول معنى الحجر في اللغة والاصطلاح، وضمنت المبحث الثاني أسباب الحجر وأنواعه ودليل كل نوع منها. وضمنت المبحث الثالث المسألة الرئيسة، وهي حكم الحجر على المرأة، وعرضت أقوال الفقهاء فيها مؤيدة بالدليل، والمناقشة قصدًا إلى ما يظن أنه الراجح، وقد رجح من آراء العلماء عدم وجوب ذلك، وإن استحب من باب حسن العشرة واستطابة نفس الزوج. وبالله التوفيق. This paper deals with an important issue which is the rule of the stone on the women of her own money in more than one-third. Ensured the first research the meaning of the stone in the language and terminology, and secured the second part, the causes and types of stone and guide each type. And ensured the third section the main issue is the rule of the stone on the women, and offered words of scholars in favor of the evidence, and discussion intentionally to what he thinks he correct view, God and conciliation. The most likely of the views of scientists is that it is not obligatory, although it is recommended as a matter of good treatment and attach same pair. God and conciliation.
Keywords: المرأة المسلمة -- الفقه الإسلامي -- المعاملات -- الحجر على الأموال -- الأحكام الشرعية